A Large‐Scale Empirical Evaluation of Cross‐Validation and External Test Set Validation in (Q)SAR. Issue 5 (3rd June 2013) - Gütlein, Martin; Helma, Christoph; Karwath, Andreas; Kramer, Stefan
Abstract (Q)SAR model validation is essential to ensure the quality of inferred models and to indicate future model predictivity on unseen compounds. Proper validation is also one of the requirements of regulatory authorities in order to accept the (Q)SAR model, and to approve its use in real world scenarios as alternative testing method. However, at the same time, the question of how to validate a (Q)SAR model, in particular whether to employ variants of cross‐validation or external test set validation, is still under discussion. In this paper, we empirically compare a k‐fold cross‐validation with external test set validation. To this end we introduce a workflow allowing to realistically simulate the common problem setting of building predictive models for relatively small datasets. The workflow allows to apply the built and validated models on large amounts of unseen data, and to compare the performance of the different validation approaches. The experimental results indicate that cross‐validation produces higher performant (Q)SAR models than external test set validation, reduces the variance of the results, while at the same time underestimates the performance on unseen compounds. The experimental results reported in this paper suggest that, contrary to current conception in the community, cross‐validation may play a significant role in evaluating the predictivity of (Q)SAR models.